FRI0156 The Combined Spondylo-Arthritis Questionnaire for Assessment of Functional Disability and Quality of Life: Assessment of the Minimal Clinically Important Difference and REAL Clinically Important Difference in Patients with Spondyloarthritis. (10th June 2014) - El Miedany, Y.; El Gaafary, M.; Sayed, S.; Ahmed, I.; Palmer, D.
Abstract : Background: The Combined Spondylo- Arthritis Questionnaire for functional disability (CASQ-Fn) and Quality of life (CASQ-QoL) Questionnaire [1] is used to assess these parameters in Spondyloarthritis (SpA) patients. Objectives: 1. To estimate the minimal clinically important differences (MCID) of the CASQ-Fn and CASQ-QoL for worsening and improvement that were experienced in SpA patients. 2. To define Real Clinical Important Difference (RCID) which reflect the degree of improvement consistent with responsiveness to therapy. Methods: 334 SpA patients (122 AS, 212 Psoriatic arthritis), starting their Biologic/DMARDs therapy and managed according to Treat-to-Target approach, completed a copy of the CASQ questionnaire at 0, 3, 6 and 12 months of therapy. Assessment of both ASDAS (for AS patients) and the ACR response criteria (for psoriatic patients) was carried out at baseline, 3, 6 and 12 months of therapy. Each of the disease activity parameters was calculated and used as external standards as follows: ([final score-baseline score]/baseline score x 100). Four categories of change were derived. 1. patients with no change or a worsening in their scores, 2. patients with a net improvement of <20%, 3. patients with a net improvement of <50%, 4. patients with a net improvement >50%. MCID was determined by estimating the mean changes in CASQ-Fn and -QoL scores in patients who showed 1 level of improvement on the disease activity parameters. RCID was determined by estimating the mean changes in CASQ-Fn and -QoL scores in patients who showed 2 levels of improvement on the disease activity parameters. Results: Depending on the external standards used, the MCID for improvement of the CASQ-Fn was -0.20 at most, whilst the MCID for worsening was +0.22 at most. Regarding CASQ-QoL the MCID for improvement was -0.21, and for worsening was +0.22 at most. RCID for improvement of the CASQ-Fn was -0.52 and for CASQ-QoL was -0.56. With adjustment for age, sex, and race, the MANOVA results linking score changes of both CASQ-Fn and CAsQ-QoL to changes in disease severity were statistically significant (p<0.01). Differences in categorical changes among both scores were also significant across the levels of change in the disease activity parameters. Logistic regression analysis revealed significant differences (p<0.01) in categorical changes (% better, %same, % worse) of both CASQ-Fn and -QoL scores across the groups that differed in the level of change in severity. Conclusions: Both CASQ-Fn and –QoL are responsive to change. The MCID of both scores for improvement as well as worsening were sensitive to important short term changes in SpA patients. The results provide insight into patient satisfaction with changes in function and expectations for therapy. RCID values are 2 to 3 times greater than MCID values. This range of MICD and RICD changes will help investigators interpret changes in CASQ-Fn and –QoL scores in clinical trials both at the group level (average change) and individual patient level (categorical change). References: Development and validation of a new questionnaire for functional impairment and quality of life assessment. Clin Exp Rheumatol. 2011; 29(5):801. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1407